Differences in employment histories between employed and unemployed job seekers - Longhi, Simonetta; Taylor, Mark (Colchester, 2010)
"We use the British Household Panel Survey (BHPS) to analyse whether employed and unemployed job seekers are substitutes by comparing their individual characteristics and past (un)employment and job histories. Since the BHPS does not directly collect information on job search activities of employed workers, we combine it with the British Labour Force Survey to assign a probability that employed respondents in the BHPS engage in on-the-job search. Even after controlling for individual heterogeneity we find important differences between employed and unemployed job seekers, both in their qualification levels and past employment histories."